Cancer mortality in kidney transplant recipients: An Australian and New Zealand population‐based cohort study, 1980–2013. Issue 10 (23rd August 2019) - Rosales, Brenda M.; De La Mata, Nicole; Vajdic, Claire M.; Kelly, Patrick J.; Wyburn, Kate; Webster, Angela C.
Abstract : Cancer burden is increasing in kidney transplant recipients, but differences in mortality compared to the general population remain unclear. We sought to compare cancer mortality in paediatric and adult kidney transplant recipients with the general population and describe any differences, by site, age and sex, country and over time. We included kidney transplant recipients from the Australian and New Zealand Dialysis and Transplantation Registry, 1980–2013. Date of death and underlying cause of death were ascertained by data‐linkage and classified using ICD10AM codes. Indirect standardisation was used to estimate standardised mortality ratios (SMR). There were 5, 284 deaths in 17, 628 kidney transplant recipients over 175, 084 person‐years of observation, including 1, 061 (20%) cancer deaths. Relative cancer mortality was higher than the general population for all‐site (SMR 2.9, 95% CI 2.7–3.1) cancer and highest for nonmelanoma skin cancer (SMR 50.9, 95% CI 43.5–59.6) and lymphoma (SMR 42.2, 95% CI 35.3–50.5). Relative cancer mortality decreased with increasing age in men ( p  < 0.001) and women ( p = 0.001) but never reached parity with the general population. Relative mortality did not change with age for skin and lip, or colorectal cancers ( p ‐value >0.1). Only relative colorectal cancer mortality increased over time ( p = 0.002). Our study shows cancer mortality in kidney transplant recipients was higher than expected in the general population. The magnitude of excess mortality varied by cancer site, age and sex. Further evidence is needed to identify whether this variation is due to differences at diagnosis or access and effectiveness of cancer treatments in this population. Abstract : What's new? While kidney transplant recipients are at increased risk of cancer, whether their risk of dying from cancer is also elevated relative to the general population remains unclear. This population study involving 17, 628 kidney transplant recipients in Australia and New Zealand shows that since 1980, cancer mortality has remained three times higher in transplant recipients compared to the general population. Relative cancer mortality risk was highest for cancers associated with immunosuppression therapy, including nonmelanoma skin cancers and lymphoma. Further investigation is needed to determine whether excess mortality may also be due to differences in diagnosis or access to cancer therapy.